Pengaruh pemberian buah naga merah, jambu biji merah, dan kombinasinya terhadap kapasitas antioksidan total dan kadar malondealdehid pada remaja perokok - Ma'arif, Mohammad Zainul; Suradi, Suradi; Sugiarto, Sugiarto (Jurnal Gizi Indonesia (The Indonesian Journal of Nutrition), 2020)
Background: Smoking habits enhance free radical in the body, which oxidize lipids to form malondialdehyde. One group that is vulnerable to smoking is adolescents. Red dragon fruit and red guava have the possibility as functional foods due to their vitamin and phytochemical content, which have antioxidant effects. This is an opportunity to prevent oxidative stress among adolescent smokers.Objectives: This study aimed to analyze the effect of red dragon fruit, red guava, and its combination to total antioxidant capacity (TAC) and malondialdehyde (MDA) levels among adolescent mild smokers.Methods: This research was an experimental study with a randomized pre-test and post-test control group design. Forty-eight subjects of male adolescent aged 16-17 years with mild smoking habits were divided into four groups: the control group (K), the intervention group with 200 grams of red dragon fruit (P1), 200 grams of red guava (P2), and the combination of both (100 grams red dragon fruit + 100 grams red guava) (P3), for 14 days. TAC examination used the DPPH method and MDA levels using the TBARS method were measured before and after the intervention.Results: After 14 days of intervention, the mean TAC was changed by -0,10±0,76 in the K group, 0,97±1,62 in the P1 group, 0,74±1,39 in the P2 group, and 0,74±1,29 in the P3 group. But the changes of TAC in all intervention groups were not significantly different from the control group (p>0,05). The mean MDA level changed by 0,229±0,371 in the K group, decreased by -0,654±0,922 in the P1 group, -0,592±0,818 in the P2 group, and -1,166±0,670 in the P3 group. The mean difference of the MDA level in all intervention groups was significantly different from the control group (p<0,05).Conclusion: Consumption of red dragon fruit, red guava, or a combination of red dragon fruit and red guava can reduce malondialdehyde levels significantly among male adolescent mild smokers. Whereas the total antioxidant capacity was changed but not significant.